Das "trevas" à luz de Fibonacci: uma visão histórica - Santos, Alberto Tadeu Acaiaba dos (2009)
The contribution of Leonardo de Pisa for the commercial mathematics of XIII century, from the publication of the Líber Abacci and the spreading of the hindu arabian numbers in the Europe in substitution to the Roman numbers, thus facilitating the commercial transactions between the peoples after the opening of the ports. We will analyze the importance of the Pisa s Leonardo de Pisa Book publication, mainly the relative aspect the commercial mathematics, the applicability of the methods of conversion developed by it, the social political moment that had favored its success and the recognition of its excellence at a time marked for a long period of ostracism. The aim of this dissertation is the analysis of the importance of the publication of the book; why of the success of the same and, although some problems even though it s time to be considered of little use the workmanship if supported during the turbulence of the period. For this he will be analyzed the problems of the book as primary source (digitalized edition) and will have theoretical subsidies from the workmanship History of the mathematics of Carl B. Boyer and will be supported in the theoretical workmanships of Dirk Struik, Rubens Gouvêa Lintz, Ubiratan D Ambrosio, Russell, the social moment and philosophical Thomas will be based in the writings of Santo Tomás de Aquino who had great influence in this period of the Europe. This project is excellent for the studies of the Mathematics History because we can verify that Science and History are strict on throughout the times, discoveries are supported or refuted, thus forming some of the fundamental questions in history of Science, of that we must reflect on the past, not to look at it with an anachronistic vision, therefore thus we will be able to understand questions and moments. When analyzing the Pisa s Leonardo book, I intend to show that science is supported at the historical moment and that if Fibonacci got success where others if had not failed, had not shown in such a way, this if must to the general contextual moment of the time. But history is not discontinued as they think, as well as nothing appears for one passes of magician, has a link that they join the ideas and accomplishments for the introduction hindu-arabic numbers in the Europe, has a social moment that determines its acceptance or and mainly it does not have the fertile mind of Fibonacci that knew to lancer the effective situations and assim to get success where others had failed, thus giving a light in the tunnel s end for a period of considered by some until the present as one period of darkness s in the scientific field